Modern Asian living - Wongvipa Devahastin na Ayudhya; Intakul, Sakul; Inglis, Kim (Singapore Periplus Editions, 2005)
Modern Asian Living features the new wave of Pan-Asian interior design that draws elements from Japanese Zen style, opulent Thai style, the best of Bali, and more. This book serves as a showcase for Asia's hottest young designers, artists, gallery owners, and furniture makers. It features floral arrangements by the world-renowned Sakul Intakul, furniture from Ou Baholyodin, artworks from Christian Liaigre, and paintings from prominent Asian artists. Ideas and tips for decorating leap off the pages, while the overall aesthetic will interest anyone enthusiastic about modern Asian style
The New Asian Design 6
TRANQUIL LIVING 11
Baan Suan Sanghob 16
Artful Living 24
Shophouse Chic 37
Cool Blue 40
Thaistyle Modem 46
Natural Organics 50
Collection 56
A Fresh Outlook 62
DRAMA 68
High Drama 70
Sky High 80
Heaven Sent 86
Highstyle Glamor 92
Candy Color 100
White 108
Intemational Appeal 114
Small is Beautiful 126
LIGHT AND SPACE 134
Lofty Sentiments 136
A Passion for Chairs 144
Customdesigned Compound 158
H1 166
White Light 178
Laidback Living 186
Strong Geometry Good 205
Acknowledgments 208
Keywords: House furnishings - Asia - History - 20th century; Interior decoration - Asia - History - 20th century; Interior decoration - Asian influences